Development of an Improved Thiosulfate-Utilizing Denitrifying Bacteria-Based Ecotoxicity Test with High Detection Sensitivity and Reproducibility - Heonseop Eom (Toxics, 2024)
Microorganism-based ecotoxicity assessment has been widely used as a reliable tool showing direct biochemical impacts of contaminants on ecosystems and the environment. The present study aimed at developing a thiosulfate-utilizing denitrifying bacteria (TUDB)-based ecotoxicity test with high detection sensitivity and favorable reproducibility. To achieve this goal, existing TUDB toxicity tests were improved by employing a pure culture of Thiobacillus thioparus ATCC 8158 and optimizing test conditions, particularly in terms of inoculated microbial biomass, incubating temperature, and operational pH. From control tests, it was found that 4 h is a sufficient processing time for TUDB test kits. As a result of optimization, 20 mg VSS/L of initial bacterial biomass, 25 °C of incubating temperature, and 6 of operational pH were determined as the most favorable test conditions, providing enhanced detection sensitivity and reproducibility. Under these optimal test conditions, I conducted toxicity tests for diverse toxic metals and obtained 0.65 ± 0.03, 1.09 ± 0.04, 1.21 ± 0.07, 0.13 ± 0.01, 0.56 ± 0.04, 1.42 ± 0.03, 0.98 ± 0.02, and 2.12 ± 0.05 mg/L of 4 h EC50 values for Ag+, As3+, Cd2+, Cr6+, Cu2+, Hg2+, Ni2+, and Pb2+, respectively. These EC50 values are substantially lower than those from earlier TUDB tests, demonstrating the high detection sensitivity of the current TUDB tests. Moreover, the present TUDB tests attained very low coefficient of variation (CV) values (1.6–6.3%) for the EC50, showing favorable reproducibility of the test methodology. In addition, the current TUDB toxicity tests offer numerous advantages for ecotoxicity assessment, including versatility for diverse test samples, no requirement for advanced equipment, and no distortion of end-point measurement. These refinements render the TUDB tests a favorable ecotoxicity assessment with enhanced sensitivity and reproducibility.